New tricks. Season eight [videorecording (DVD)] - Armstrong, Alun; Bolam, James, 1935-; Redman, Amanda, 1957-; Waterman, Dennis, 1948 February 24- (Acorn Media, 2012)
The hit British crime series returns with new mysteries. Aging cops and traditional sleuthing trump high-tech gadgets and modern criminology. As one of the most-watched shows on British television, New Tricks features strong writing, wry humor, and a splendid cast.